2015
DOI: 10.1902/jop.2015.150346
|View full text |Cite
|
Sign up to set email alerts
|

Relative Composition of Fibrous Connective and Fatty/Glandular Tissue in Connective Tissue Grafts Depends on the Harvesting Technique but not the Donor Site of the Hard Palate

Abstract: Despite high interindividual variability in terms of relative tissue composition in the hard palate, DE-harvested CTG contains much larger amounts of CT and much lower amounts of FGT than SF-harvested CTG, irrespective of the harvesting site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0
14

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(111 citation statements)
references
References 28 publications
3
94
0
14
Order By: Relevance
“…Interestingly, the most noticeable differences between both groups were observed from 5 to 7 mm apical to the healing abutment favouring TG. This outcome could be expected, as it is known from histological studies (Bertl et al., ; Yu et al., ) that the closest area to the palatal gingival margin contains higher amounts of lamina propria compared to more apical areas which seem to contain more glandular and fatty tissue. In contrast, TA appears to contain more lamina propria in its whole dimension.…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, the most noticeable differences between both groups were observed from 5 to 7 mm apical to the healing abutment favouring TG. This outcome could be expected, as it is known from histological studies (Bertl et al., ; Yu et al., ) that the closest area to the palatal gingival margin contains higher amounts of lamina propria compared to more apical areas which seem to contain more glandular and fatty tissue. In contrast, TA appears to contain more lamina propria in its whole dimension.…”
Section: Discussionmentioning
confidence: 73%
“…15 The authors suggested that the FGGT approach can be performed regardless of fibromucosa thickness and that the quality of the DeCTG may be superior than a SCTG which is harvested deeper and contains less lamina propria and more fatty and glandular tissue. 15,26 Despite its clinical significance remains unknown, it has been shown that DeCTG may include epithelial remnants. 27 In the literature, however, whether one harvesting technique is superior to the other, remains controversial and their comparison has always been investigated in terms of postoperative morbidity or root coverage outcomes.…”
mentioning
confidence: 99%
“…An RCT in 2010 compared root coverage outcomes of CTG obtained by the trapdoor approach with CTG obtained by de-epithelization of FGG (12). There were Yoshino et al: CO 2 Laser De-epithelization for SCTG 871 (13). They concluded de-epithelialization harvested CTG contains much higher amounts of connective tissue and much lower amounts of fatty/glandular tissue than CTG harvested with split-flap preparation.…”
Section: Discussionmentioning
confidence: 99%